Development of a biology diagnostic test using case study and item response theory three-parameter logistic model - Mirabete, Glen S. (College of Education, University of the Philippines Diliman, 2021)
Testing is among the essential components of assessment. Test results assess students' knowledge and skills in learning the content of the subject area and help teachers identify the students' learning difficulties. This study developed the Biology diagnostic test for STEM students using the mixed method exploratory sequential and item response theory three-parameter logistic (IRT-3PL) model. This study intends to provide valid and reliable test material for General Biology 2 in Senior High School STEM classes. Cases of students who experienced learning difficulties in Biology were considered to determine the test items under specific topics and content areas. Biology teachers were interviewed regarding the students' challenges and their concerns in teaching the subject. Focus group discussion was conducted for both teachers and students to determine the pool of items and formulating the biology test questions. Results showed that students have varying difficulties in learning biology, and specific topics and content areas were found difficult and were noted and included in the test table of specifications. The content-validated test items based on the learning difficulties were tried out to 1240 students in the academic year 2019-2020. The reliability of the Test based on Kuder-Richardson 20 (KR-20) is 0.848 is considered acceptable. Discrimination and difficulty indices were considered, and findings showed that 50 items must be retained. Options and distractor analysis revealed that certain items must be reviewed as there are options that are not plausible enough. Some distractors were attractive among the higher ability group than the lower ability group. The items were further evaluated using the item response theory to determine the item characteristic curve (ICC), item information function (IIF, and the test information function (TIF). There were eight (8) groups of items considered under specific ability and subject content areas. The guessing parameter considered in the three-parameter logistic model revealed that difficult items are prone to guessing among the lower ability group. Very easy and very difficult items have low discriminating power. Considering the difficulty and discrimination indices, easy, difficult, and desirable items are acceptable with good and excellent discriminating power. Results of the study aim to shed light and contribute to the innovative processes in test development and educational assessment using the more advanced and comprehensive mixed-method exploratory approach.